The influence of hydrogen addition on the combustion characteristics of a common-rail CI engine fueled with waste cooking oil biodiesel/diesel blends - FEYZİOĞLU, AHMET; YILMAZ, İLKER TURGUT (Elsevier B.V., 2021)
In this study, the effect of hydrogen assisted intake air on combustion characteristics of a diesel fuel-waste cooking oil biodiesel (WCOB) blend fueled CI engine has been extensively studied. While the diesel and B25 (75% diesel fuel+25% WCOB) fuels used as the main fuel were sprayed directly into the cylinder, the hydrogen, the secondary fuel was mixed with the intake air at 10, 20, 30 and 40 lpm flow rates and taken into the cylinder. The maximum in-cylinder pressure (CP) values decreased with B25 fuel compared to diesel fuel. But B25‑hydrogen dual-fuel mode operation exhibited higher maxium CP and RoPR value according to diesel fuel. It was seen that hydrogen has a more significant effect on premixed pilot fuel combustion phase compared to the diffusion combustion phase. It was observed that the combustion duration (CD) of neat B25 fuel lower than that of diesel fuel, generally. In case of B25‑hydrogen dual-fuel mode operation, CD increased depending on increasing hydrogen addition rate. It was seen that hydrogen enrichment has no adverse effect on ringing intensity (RI). © 2021 Elsevier B.V.
Keywords: Combustion characteristics; Common rail CI engine; Heat release; Hydrogen enrichment; Waste cooking oil biodiesel